High Detectivity from a Lateral Graphene–MoS2 Schottky Photodetector Grown by Chemical Vapor Deposition. (16th July 2018) - Deng, Wenjie; Chen, Yongfeng; You, Congya; Liu, Beiyun; Yang, Yanhan; Shen, Gaoliang; Li, Songyu; Sun, Ling; Zhang, Yongzhe; Yan, Hui
Abstract: 2D material–based photodetectors have demonstrated the great potential in future optoelectric applications and the compatibility with the traditional semiconductor technology. However, low detectivity and difficulty of large‐scale fabrication still limit their application. Here, an ultrasensitive in‐plane lateral graphene–MoS2 heterostructure is successfully constructed using one‐step growth by chemical vapor deposition, which is suitable for large‐scale fabrication. The Schottky junction is formed in the channel with the edge contact of graphene and MoS2 . It displays good rectification characteristics with an on/off ratio up to 10 6 . As a photodetector, it exhibits excellent detectivity with the specific detectivity D* up to 1.4 × 10 14 Jones and the responsivity of 1.1 × 10 5 A W −1, which benefit from strong absorption, the efficient separation of the photoexcited carriers, and quick charge transport in the Schottky junction device. Moreover, heterostructure photodetector array is demonstrated here which shows the large‐scale fabrication capacity. All of these results prove the potential of 2D material–based junction devices for optoelectronic devices. Abstract : High performance of 2D material–based photodetectors is important for their application. An ultrasensitive lateral graphene–MoS2 heterostructure Schottky photodetector is constructed, whose specific detectivity and responsivity range up to 10 14 Jones and 10 5 A W −1, respectively. Moreover, a heterostructure photodetector array is demonstrated here, showing the large‐scale fabrication capacity. The results prove the potential of 2D materials for future optoelectronics application.